SISTEM INFORMASI AKUNTANSI PERSEDIAAN BAHAN BAKU UNTUK PENGENDALIAN BIAYA PERSEDIAAN DENGAN PERIODIC REVIEW METHOD BERBASIS MULTIUSER DI PT. SANGO CERAMICS INDONESIA - Sri Wahyuning Wahyuning; Sri Puji Wijayanti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The inventory system is one of the most important managerial functions, because the majority of companies involve large investments in this aspect, as well as for PT Sango Ceramics Indonesia which uses a lot of inventory in the field of planning and controlling its inventory costs. PT Sango Ceramics Indonesia is a company engaged in the ceramic industry. Problems that often occur so far include the company not determining the frequency of ordering raw materials and storing raw materials, as a result the costs incurred by the company for ordering raw materials are quite high, and the absence of a safety stock to anticipate uncertain inventory needs. The Periodic Review method is a method that can help the process of controlling raw material inventory costs. This method uses an approach to the concept of the number of orders economically used in each period which is a diverse demand. The application of the Periodic Review Method (R, s, s) policy on the inventory system is able to produce a lower total inventory cost, order volume and inventory levels in a balanced manner. . Judging from these problems, the authors need to redesign the stock information system using a computer-based system, namely Microsoft Visual Basic. System design using Qlient Server which consists of input design, system design and procedure, output design fiber. This new system is expected to be able to overcome the weaknesses of the previously used information system.